The influence of technological innovative capabilities on firm performance: Moderating effect of strategic agility - Hamza Khraim (Problems and Perspectives in Management, 2022)
This study investigates the influence of technological innovative capabilities (TICs) on firm performance (FP) in the IT sector, with strategic agility as a moderator variable. This paper analyzes the TICs at the firm level in the service sector using the functional approach. An online structured questionnaire was adapted and refined to collect the required information on the influence of TICs dimensions on FP in the IT sector to achieve the objectives. The unit of analysis consists of top management staff and heads of departments from IT firms in Amman, Jordan. A sample of 67 IT firms was selected, and 300 questionnaires were distributed. A total number of returned responses was 223, producing a 74% response rate. Structural equation modeling was used to test the hypotheses. The revealed findings show that learning capability, marketing capability, organizational capability, and strategic planning capability had a significant influence on FP, whereas resource allocation capability was not significant. In addition, multiple hierarchical regression was used to test the moderating effect of strategic agility on the relationship between TICs and FP. Revealed results of the overall model to examine the moderating effect show that strategic agility is not significant in moderating the relationship between TICs dimensions and FP.